Analytical Modelling and Performance Analysis of Dielectric Pocket-Induced Double-Gate Tunnel Field-Effect Transistor. Issue 1 (2nd January 2019) - Saha, Priyanka; Kumari, Tripty; Sarkar, Subir Kumar
ABSTRACT: In this paper, a dielectric pocket-induced double-gate tunnel field-effect transistor is presented for improving the ON state current and suppressing the ambipolar conduction of the device. Introduction of dielectric pocket at the junction of both source and drain helps to tune the tunnelling barrier and subsequently controls the tunnelling current. A physics-based analytical model of surface potential and electric field is deduced by solving 2D Poisson's equation.Tunnelling current is then derived using Kane's model. The performance of this structure is then studied by varying the dielectric material of the pocket at source/drain junctions. Analytical results have been compared with the SILVACO ATLAS simulated results for verification of our model.